Coordinated Converter Control Strategy in Hybrid AC/DC Power Systems for System Frequency Support. (September 2016) - Endegnanew, Atsede G.; Uhlen, Kjetil
Abstract: This paper proposes a coordinated converter control strategy for multi-terminal dc (MTDC) grids in hybrid AC/DC power systems. Previous works have shown the possibility of providing frequency containment reserve (FCR) from offshore wind farms to ac grids through MTDC grids using frequency and dc voltage droop control. However, due to the characteristics of dc voltage droop control, the frequency support would come both from offshore wind farms and all other ac grids connected to the MTDC. This paper proposes a coordinated MTDC converter control strategy that maximizes the share of the FCR contribution from an offshore wind farm and reduces the contribution of other ac grids. A hybrid AC/DC power system consisting of offshore wind farm and two asynchronous grids connected through an MTDC grid is used as a test system. Using the test system, different scenarios are analyzed to demonstrate the performance of the proposed coordinated control strategy.